Evaluation of the results of the proximal femoral nail surgery for intertrochanteric femur fractures - Ulusoy, İbrahim; Kıvrak, Aybars; Yılmaz, Erhan (My University, 2022)
This study aimed to evaluate the clinical, functional, and radiological results of the patients who underwent proximal femoral nail (PFN) surgery due to intertrochanteric\rfemur fractures (IFF). A total of 195 patients who underwent PFN surgery due to IFF in January 2014 and January 2018 in our institute and with at least six months\rfollow-up periods were included in the study. Demographic data, comorbidities, Evans-Jensen fracture classification, anesthesia risk scores, hospitalization duration,\rtime to surgery, duration of surgery, amount of blood loss, whether additional traumas exist, quality of reduction, complication rates, Harris hip scores (HHS), Fogagnolo\rReduction Quality criteria and possible correlations between these variables were evaluated retrospectively. In our study, the majority of the patients were found to be\rbetween the ages of 70-90. Hypertension was found to be the most common comorbid disease in the patients (50.2%). The fracture type of the majority of the patients was\rdetermined as type 4. The majority of patients were identified as ASA III and ASA IV group patients (38.4% and 35.9%, respectively). Successful HHS was found at a rate\rof 77.5%. As the fracture type worsened, the HHS score worsened (p<0.05). Reoperation rates were significantly lower in those with good reduction quality than those with\rpoor reduction (p<0.05). A significant association was found between the overall complication rate and reduction quality (p<0.05). A significant and negative correlation\rwas found between HHS scores and total complication rates (p<0.05). Intertrochanteric femur fractures are frequently encountered by orthopedists. These fractures, which\rrequire surgical intervention in almost all of them, are important because the population is old and prone to complications, and accurate and rapid surgical intervention is\rrequired. Our results suggest that PFN surgery is an appropriate choice for IFF.
Keywords: Genel ve Dahili Tıp; Ortopedi